Evaluation of the HIV 'Test and Treat' strategy in Men who have Sex with Men in West Africa. - (:unkn) unknown (My University, 2021)
In West African countries, HIV epidemic is mixed or concentrated in key populations including men who have sex with men (MSM). Since 2010, the World Health Organization (WHO) has recommended to West-African health decision-makers targeting MSM as part of the response to the HIV epidemic. It recommends to propose comprehensive prevention programme including “HIV infection Test and Treat strategy”. HIV testing is a key step in the fight against HIV. It allows to classify as negative or positive the person who undergo it, and then propose the suitable intervention. In addition, when it is regularly administered, it could allow the detection of acute HIV-infection. As of 2015, the WHO has recommended antiretroviral therapy (ART) initiation in all HIV-infected adults irrespective of their clinical stage and CD4 cell count. The “HIV infection Test and Treat strategy” includes these two components of fight against HIV. However, data on HIV infection “Test and Treat” strategy in MSM are lacking. Our work which is performed from “CohMSM ANRS 12324-Expertise France” project aim to assess the HIV infection “Test and Treat” strategy in MSM in West Africa.Our findings show that HIV seronegative MSM adherence to quarterly follow-up visits including HIV testing is good. However, overall HIV incidence remains high as well as specifically by study site. In addition, adherence to quarterly follow-up visits has no impact on new HIV infections. Almost all the HIV seropositive MSM discovering their HIV status accept the proposition to initiate ART immediately. Among them, one quarter initiate it the same day, two third initiate it rapidly (i.e. within seven days of HIV diagnosis). However, retention on ART is sub-optimal. Rapid ART initiation is favorable to HIV viral suppression over time. However, it has neither impact on retention on ART nor on immunologic response.Our study highlights that it is urgent to strengthen HIV prevention services by addin
Keywords: African Research